Exploring Therapeutic Change in Indian Clients Experiencing Emotional Abuse: A Social Justice Approach to Counselling. - Cheguvera, Natania; Arur, Aditi Ashok (Counselling & Psychotherapy Research, 2025)
Background: This study examined the lived experiences of emotional abuse (EA) in Indian parent‐adult child relationships, emphasising the intersection of systemic influences in maintaining EA. Employing a social justice framework, the research explored pathways to foster 'change' at both individual and societal levels to address EA. Methods: Data were collected through semi‐structured interviews with ten participants undergoing therapy, and analysed using Interpretative Phenomenological Analysis. Results: Four master themes emerged: 'State of Lack', 'Lack of Relatability to Gender and Culture Norms', 'Therapy as a Catalyst for Regaining Sense of Self and Empowerment', and 'Cultural Shifts, Therapeutic Integration and Redefining Norms to Address Emotional Abuse'. Conclusion: The findings emphasise the contribution of gender and cultural norms in the reinforcement of EA, while highlighting therapy's potential in fostering individual healing while advocating for societal transformation. Our study adds valuable literature to the fields of counselling, social justice research, cultural psychology, social psychology, and feminist psychology, and provides a basis for future research.